The effective CIO how to achieve outstanding success through strategic alignment, financial management, and IT governance - Brown, Eric J. (CRC Press, 2009)
Links theoretical scaffolding with effective IT management implementation. This title helps to dissolve the negative image many CIOs have as remote, purely rational decision machines, while demonstrating how to improve quality and throughput in your business. It includes interviews with highly successful CIOs.